FAKTOR PENYEBAB REMAJA MENGKONSUMSI MINUMAN KERAS DI JORONG PASA NAGARI ALAHAN MATI KECAMATAN SIMPATI KABUPATEN PASAMAN - AHDA, MAULA AUFITRI (Pendidikan Sosiologi, 2014)
The background The background of the research is the tenageer usually consume the liguor. This matter they do without recognizing the time, both noon and night. The tenageer consume that liguor together, they do this in intersecting street small shop. The purpose of the reseaich is to describe the factor make the tenageer consume in Jorong Pasa Nagari Alahan Mati Kecamatan Simpati Kabupaten Pasaman.This research use association of differential theory stated by Edwin Sutherland. This research use qualitative reseaich with descriptive type. The informan in this reseatch are 21 tenageer that 17-21 years old and they like hang out in small shop and they consume the liguot. Next, elite figure as the supporting informan. This reseatch use purposive technigue sampling in choose informan. The reseacher used primary and secondary kind of data. The researcher used observation (non participant obsevation) interview and documentation in collecting of data. Analysis unit is individual. The researcher used interactive data analysis models. (Miles & Huberman) with the steps such as : (1) Collecting of data, (2) reduction of data, (3) shared the data, (4) condusion. The result of the reseaich is there are several factors make the tenageer consume liguot such as : broken home family, high curriousity, in attentive of parent, disappoint ted release, easy to get liguor, envirotment, mass media, differentiate of culture.